Educational status and empowerment of Muslims - Nazeerdeen, S., 1953- (New Delhi : Discovery Pub. House, 2012)
Study conducted in Tiruchchir$1iTK(Bpalli and Thanjavur Districts of Tamil Nadu, India.s
Includes bibliographical references (p. [207]-213) and index.
Keywords: Muslims -- Education -- India -- Tiruchchirappalli (District) -- History; Muslims -- Education -- India -- Thanjavur (District) -- History; Muslims -- Government policy -- India -- Tiruchchirappalli (District).; Muslims -- Government policy -- India -- Thanjavur (District).